Choreographing rhizosphere effect with agricultural practices for agroecology? - Edith Le Cadre; Sebastian Mira; Xiaoyan Tang; Mathieu Emily (PLoS ONE, 2025)
For sustainable agriculture, soil-plant interactions (i.e., the rhizosphere effect) is prominent focus, since they determine plant health and nutrition. However, system-level agricultural management practices interfere with the rhizosphere effect. In this study, we characterized the rhizosphere effect of winter wheat (Triticum aestivum var. LG Absalon) on farm fields along two levels of crop diversity induced by rotation (high or low) combined with two tillage intensities (conventional or reduced). The rhizosphere effect was determined from differences in enzyme activities involved in carbon (β-glucosidase), nitrogen (arylamidase) and phosphorus (acid phosphatase) cycles measured in the rhizosphere and bulk soil. We observed positive rhizosphere effects for all enzymes, but they were significantly altered by soil tillage. High temporal diversification and reduced tillage increased the intensity of the rhizosphere effect for all enzymes studied, suggesting the relevance of agroecological management of arable land to promote nutrient cycling. In contrast, benefits of crop diversification on the rhizosphere effect decreased drastically under conventional tillage. Accordingly, the rhizosphere effect should be carefully synchronize with agricultural practices under agroecological transition.